Preservation of the Heritage: Survival and Documentation by Palestinians (American Journal of Islam and Society, 2009)
Books Reviewed: Kamal Boullata and Kathy Engel, eds. We Begin Here:Poems for Palestine and Lebanon. Northampton, Massachusetts: Interlink,2007; Nadia G. Yaqub. Pens, Swords, and the Springs of Art: The OralPoetry Dueling of Palestinian Weddings in the Galilee. Leiden and Boston:Brill, 2007; Laleh Khalili. Heroes and Martyrs of Palestine: The Politics ofNational Commemoration. New York: Cambridge University Press, 2007.The Israeli-Palestinian conflict, which hasmade headlines for decades, showsno sign of abating, for each side is convinced that it is in the right anddemands to live upon its ancestral land. The Palestinian “problem,” whichhas produced a plethora of books, goes back to Israel’s 1948war of independenceand remains unresolved. In this essay, I shall review two books that dealdirectly with the Palestinian problem and their overall situation (especially ofthe Palestinian refugees in Lebanon) and one on oral poetic duels amongPalestinians in Israel. This latter book provides some between-the-linesinsights about how Israeli Arabs cope with the Palestinian problem ...